Kedudukan berkuasa dan hak milik dalam sudut pandang KUH Perdata. Seri hukum harta kekayaan - MULJADI, Kartini (Kencana, 2004)
Kedudukan berkuasa dan hak milik dalam sudut pandang KUH Perdata. Seri hukum ...